7.3k views
1 vote
Determine the voltage across a 2-μF capacitor if the current through it is i(t) = 3e−6000t mA. Assume that the initial capacitor voltage is zero g

1 Answer

7 votes

Answer:


v = 250[1 - {e^(-6000t)}] mV

Step-by-step explanation:

The voltage across a capacitor at a time t, is given by:


v(t) = (1)/(C) \int\limits^(t)_(t_0) {i(t)} \, dt + v(t_0) ----------------(i)

Where;

v(t) = voltage at time t


t_(0) = initial time

C = capacitance of the capacitor

i(t) = current through the capacitor at time t

v(t₀) = voltage at initial time.

From the question:

C = 2μF = 2 x 10⁻⁶F

i(t) = 3
e^(-6000t) mA

t₀ = 0

v(t₀ = 0) = 0

Substitute these values into equation (i) as follows;


v = (1)/(2*10^(-6)) \int\limits^(t)_(0) {3e^(-6000t)} \, dt + v(0)


v = (1)/(2*10^(-6)) \int\limits^(t)_(0) {3e^(-6000t)} \, dt + 0


v = (1)/(2*10^(-6)) \int\limits^(t)_(0) {3e^(-6000t)} \, dt


v = (3)/(2*10^(-6)) \int\limits^(t)_(0) {e^(-6000t)} \, dt [Solve the integral]


v = (3)/(2*10^(-6)*(-6000)) {e^(-6000t)}|_0^t


v = (-3000)/(12) {e^(-6000t)}|_0^t


v = -250 {e^(-6000t)}|_0^t


v = -250 {e^(-6000t)} - [-250 {e^(-6000(0))]


v = -250 {e^(-6000t)} - [-250]


v = -250 {e^(-6000t)} + 250


v = 250 -250 {e^(-6000t)}


v = 250[1 - {e^(-6000t)}]

Therefore, the voltage across the capacitor is
v = 250[1 - {e^(-6000t)}] mV

User Alepac
by
5.7k points